Economic and Legal Aspects of Environmental Safety - VINOGRADOVA, Elena Valeryevna; MUKHLYNINA, Maria Mikhailovna; MUKHLYNIN, Dmitry Nikolaevich; SOLOVYEVA, Natalia Vladimirovna; LEBEDEVA, Olga Yevgenievna (Journal of Environmental Management and Tourism, 2018)
The paper is devoted to the economic and legal aspects of environmental safety in modern conditions. It is proved that there are the necessary initial data and rationalizing materials for the introduction in accordance with the established procedure of the normative indicators of the lower threshold of environmental safety. It has been established that in the economically developed countries considerable experience in recycling household waste has been accumulated. It is determined that there are all grounds to assert that, at the present level of development of science and technology, it is technologically possible to ensure environmental safety through the rational use of natural resources, the introduction of wasteless complexes, resource and energy-saving facilities. Practice has shown that in the legislation of the Russian Federation the issues of rational use of natural resources are poorly reflected. These issues were studied in detail in the governmental plans, which in the previous period had the status of laws.